FIRST CANCER STATISTICS REPORT FROM HAZARA DIVISION - Ahmad, Sheraz; Qureshi, A. Nadim; Kazmi, Abida; Rasool, Ahsan; Gul, Mahwish; Ashfaq, Muhammad; Batool, Laila; Rehman, Raana Abdur; Ahmad, Jawad; Muniba, Muniba (Journal of Ayub Medical College Abbottabad, 2013)
Background: ’˜Cancer’ is on rise globally. Cancer registry is vital for policy making, resource allocation, progress tracking and overall cancer control. In Pakistan, cancer prevention, screening and standardised clinical trials, as well as quality assurance through surveillance are badly hampered due to the lack of a National Cancer Registry. For Pakistan a well-integrated system of Cancer Registry is need of the day. Methods: This retrospective study was conducted on the hospital records at the Oncology Department of Ayub Teaching Hospital, Abbottabad from year 2007-12. Data were collected through a standard data capture form with a final figure of 555 patients. The malignancies were diagnosed clinically and histo-pathologically at different laboratories of Pakistan. Results: Among these cases, 54.08% were male and 45.92% female. Incidence of cancer in patients below 14 years age was 8.47% and 91.53% above 14 years. Majority (31.95%) cases were from Mansehra followed by Abbottabad with 27.08% and Haripur 14.26% cases. Leukaemias were at top with 15.14% cases followed by breast carcinoma (13.69%), Lymphomas (12.07%), ovarian carcinomas (8.65%), and gastric carcinoma and skin cancers with 2.70% each. Among men, the highest incidence was of Hodgkin’s lymphoma (14.9%) followed by lymphocytic leukaemia (14.3%). Prostate cancer was seen in 8.3% male patients. Another 5.7% patients had lung cancer. In women, the highest incidence was carcinoma breast (19.7%) followed by ovarian carcinoma (13.4%), leukaemia (9.7%), and Hodgkin’s lymphoma (4.3%). Conclusion: A variety of cancers are prevalent in the indigent population. Record-keeping in wards is sub-optimal. Commonest cancers in the area have slight differences with rest of the country. Keywords: Cancer, Cancer Registry, Abbottabad, Hazara, Pakistan